Psychometric Analysis for Chemical Kinetics Multiple Choice Questions - Luca D’Ottone; Enunuwe Chuckunoye Ochonogor (Orbital: The Electronic Journal of Chemistry, 2019)
The aim of this study is to research the effectiveness of MCQs as a testing tool for undergraduate chemical kinetics. This study analyses psychometric indicators of a 30 multiple choice questions (MCQs) test focused on chemical kinetics, and compares those indicators with the ones calculated for commonly accepted American Chemical Society (A.C.S.) inorganic chemistry test. The study group consists of first and second year General and Inorganic Chemistry students of a major college in the Southeast region of the United States of America (N=68). Quasi-experimental design was used for this research. After authorization of the Institutional Research Board of the institution was secured, a group of 104 students was ask to participate. Out of these, only 68 decided to move forward and participate in the testing. The participants, after being exposed to different study materials were tested on their understanding of chemical kinetics with a 30 MCQs test.  The psychometric indicators for the 2015 General Chemistry ACS standardized test were calculated from information available on the official web site of the ACS Examination Institute (EI). The MCQs test built on a battery of 30 questions of the present study demonstrate to have an accepted difficulty level (p=51.08), good internal consistency (KR-20= 0.76), but low discriminatory power (D=0.14). The results of the MCQs test built for this study are generally consistent with the benchmark that can be inferred from the ACS EI data, and underscore the fact that undergraduate chemical kinetics can be effectively tested via a battery of MCQs.DOI: http://dx.doi.org/10.17807/orbital.v11i1.1323